Internal Quality Control on Leukocyte Count at UPTD Health Laboratory, Sleman, DIY - Prasetya, Hieronymus Rayi; Nurlaili Farida Muhajir; Seprianto Maloko; Sri Murtiningrum (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Background: Hematology analyzers (HA) are used for automated leukocyte counts, but are subject to errors if nucleated erythrocytes, fibrin precipitation, or prolonged sample sitting are present. Quality control is required to ensure accuracy of results. The clinical laboratory of the UPTD Health Laboratory of Sleman Regency, DIY has carried out quality control but has not involved Levey-Jennings control charts and six sigma analysis. This study aims to determine the internal quality assurance of the analytical stage of the HA device in the examination of leukocyte counts in that laboratory. Methods: This type of research is a descriptive study with the subject of the HA Sysmex XP-100 tool. The variables of this study are data from the quality control results of automatic leukocyte count examination in February-March 2024. Data analysis includes calculation of six sigma values, creation of Levey-Jennings control charts and evaluation using westgard rules. Results: The results showed that the examination of the number of leukocytes with the HA tool had an accuracy of 99.45% and a precision of 98.49%, while for the evaluation of the Levey-Jennings graph with the westgard rule at the normal level control, there was a rule of 12s on day 3 and 13s on day 6. Six sigma analysis shows that the performance of the tool for examining the number of leukocytes is at world class level with an average sigma value of 12.42. Conclusion: This Based on the results, it can be concluded that the examination of leukocyte counts with the HA Sysmex XP-100 at the Sleman Regency Health Laboratory UPTD, DIY has an accuracy of 99.45% and a precision of 98.49%. Evaluation of the Levey-Jennings control chart and Six Sigma analysis showed world-class performance, indicating that this tool provides excellent performance and meets international quality standards.